THU0182 Single Dose? Multiple Doses? Comparison of MTX-PG Concentration, Safety and Efficacy in Patients with Rheumadoid Arthritis Between Single- and Divided Dosage Regimens. (9th June 2015) - Ihata, A.; Kobayashi, K.; Osada, A.; Sakuma, H.; Tsuji, F.; Yoshimura, T.; Setoguchi, C.; Okamoto, M.; Nagaoka, S.
Abstract : Background: Methotrexate (MTX) has been well-known anchor drug for rheumatoid arthritis (RA), however, dose regimen varies and it depends on countries. The divided dosage of MTX was frequently prescribed in Japan, however, the differences of safety and efficacy between divided and single dose regimens were not fully examined. Objectives: We conducted a preliminary study for RA patients to compare the safety, efficacy profile and MTX-polyglutamates (PGs) concentration between single- and divided dosage regimens. Methods: Single-center Random Controlled Trial was designed. Thirty-one patients who had been insufficiently controlled by MTX (8 mg/week) were randomly assigned to 2 groups (single dose regimen/week: 15 patients; three-dose regimen/week: 16 patients). MTX dose of all patients was allowed to increase up to 16 mg/week. Safety and efficacy parameters (adverse events, the elevation of liver function tests (LFTs), WBC counts and DAS28 were monitored at baseline, 4, 8, 12 and 19 weeks. MTX-PGs in red blood cells were also detected by LC-MS/MS at same interval. Results: There were no significant differences in the average of age (66.3±9.2yr), disease duration (5.8yr), and baseline DAS28(CPR) (2.84±0.98) between two groups. There were also no differences in the improvement of DAS28(CPR) between two groups (-0.95±1.66 vs -0.75±1.09 respectively) and weekly MTX dose (11.5±1.6mg/week vs 11.4±1.4mg/week). Three adverse events were observed only in 3-dose regimen group (18.8%, increase in LTFs). The remarkable difference was observed in MTX-PGs, 3-dose regimen group showed significantly higher concentration of MTX-PG1+2 than single-dose group. On the other hand, 3-doses regimen group showed slight lower MTX-PG4+5 than single-dose regimen group, and there was no difference in MTX-PG3. Conclusions: The efficacy did not show significant difference between two groups. Liver function may be affected by concentration of MTX-PG1+2, which elevated in divided dosage regimen group. Further investigation is required in a larger population. Acknowledgements: Clinical registration: UMIN000012473 Disclosure of Interest: A. Ihata: None declared, K. Kobayashi: None declared, A. Osada: None declared, H. Sakuma: None declared, F. Tsuji Employee of: Santen Pharmaceutical. CO., Ltd., T. Yoshimura Employee of: Santen Pharmaceutical. CO., Ltd., C. Setoguchi Employee of: Santen Pharmaceutical. CO., Ltd., M. Okamoto Employee of: Santen Pharmaceutical. CO., Ltd., S. Nagaoka: None declared